2013
DOI: 10.3389/fpsyg.2013.00581
|View full text |Cite
|
Sign up to set email alerts
|

Severity of specific language impairment predicts delayed development in number skills

Abstract: The extent to which mathematical development is dependent upon language is controversial. This longitudinal study investigates the role of language ability in children's development of number skills. Participants were 229 children with specific language impairment (SLI) who were assessed initially at age 7 and again 1 year later. All participants completed measures of psycholinguistic development (expressive and receptive), performance IQ, and the Basic Number Skills subtest of the British Ability Scales. Numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
0
32
1
2
Order By: Relevance
“…Although there is a debate on the role of language in mathematics, the trend seems to emerge toward a consensus that mathematical development partly depends on language (see Durkin, Mok, & Conti-Ramsden, 2013 for a short overview). Indeed, next to cognitive child factors, linguistic abilities have also been found to be related to numeracy (Dehaene, Piazza, Pinel, & Cohen, 2003), and in fact predict mathematical abilities over time.…”
Section: Individual Differences In Early Numeracy Skillsmentioning
confidence: 99%
“…Although there is a debate on the role of language in mathematics, the trend seems to emerge toward a consensus that mathematical development partly depends on language (see Durkin, Mok, & Conti-Ramsden, 2013 for a short overview). Indeed, next to cognitive child factors, linguistic abilities have also been found to be related to numeracy (Dehaene, Piazza, Pinel, & Cohen, 2003), and in fact predict mathematical abilities over time.…”
Section: Individual Differences In Early Numeracy Skillsmentioning
confidence: 99%
“…A longitudinal study of Durkin et al indicates that severity in SLI is closely related to mathematical deficits [3]. The authors demonstrated that those children with SLI who progressed less in their language compared to their peers within one school year also advanced less in their mathematical skills.…”
Section: Determinants For Arithmetic Skillsmentioning
confidence: 98%
“…Specific developmental disorders of speech and language are often followed by associated problems, such as difficulties in reading and spelling (…)" [4]. Note that this definition does not mention mathematics although recent studies demonstrate the association of SLI with deficits in mathematical learning in many children [2] [3].…”
Section: Challenges Of Mathematical Learning For Children With Slimentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to cross-domain influences LeFevre et al (2013) showed a reliable impact of children's spatial abilities on numerical skills. Additionally, Durkin et al (2013) observed that language ability is a unique predictor of actual and future numerical achievement. Getting closer to the domain of numerical cognition, Lafay et al (2013) found that finger counting may be useful but not necessary to develop accurate symbolic numerical competencies.…”
mentioning
confidence: 99%